Crystallographic characterization of the (R)‐selective amine transaminase from Aspergillus fumigatus. (1st April 2014) - Thomsen, Maren; Skalden, Lilly; Palm, Gottfried J.; Höhne, Matthias; Bornscheuer, Uwe T.; Hinrichs, Winfried
<x xml:space="preserve">Abstract</x> The importance of amine transaminases for producing optically pure chiral precursors for pharmaceuticals and chemicals has substantially increased in recent years. The X‐ray crystal structure of the (R)‐selective amine transaminase from the fungus Aspergillus fumigatus was solved by S‐SAD phasing to 1.84 Å resolution. The refined structure at 1.27 Å resolution provides detailed knowledge about the molecular basis of substrate recognition and conversion to facilitate protein‐engineering approaches. The protein forms a homodimer and belongs to fold class IV of the pyridoxal‐5′‐phosphate‐dependent enzymes. Both subunits contribute residues to form two active sites. The structure of the holoenzyme shows the catalytically important cofactor pyridoxal‐5′‐phosphate bound as an internal aldimine with the catalytically responsible amino‐acid residue Lys179, as well as in its free form. A long N‐terminal helix is an important feature for the stability of this fungal (R)‐selective amine transaminase, but is missing in branched‐chain amino‐acid aminotransferases and D‐amino‐acid aminotransferases.